Development of pre-service teachers’ noticing competencies within a mathematical modelling context: a case study - Alwast, Alina (2021)
Mathematical modelling is challenging for students as well as for teachers. Thus, fostering teachers’ competencies to teach mathematical modelling is an essential component of teacher education. Recent research on teachers’ competencies pays increasing attention to the role of noticing conceptualised as situation-specific competencies necessary for actions within the classroom. These situation-specific noticing competencies are needed for the teacher to react to unanticipated approaches and unforeseen obstacles students may encounter when working on modelling problems. To assess these competencies, videos can be used to simulate real classroom situations and measure the skills necessary for a spontaneous and adequate diagnosis and action. In this paper, the development of pre-service teachers’ noticing competencies within a mathematical modelling context is analysed by qualitatively comparing pre- and post-test data. A modelling seminar at the master’s level served as an intervention. Three pre-service teachers were selected, and their competence development is analysed qualitatively in-depth regarding growth indicators. The pre-service teachers showed different trajectories of learning. These were manifested in different ways and differed concerning the topics of students’ difficulties, use of metacognitive strategies and approaches used to solving the problem.